Effects of acute and chronic interval sprint exercise performed on a manually propelled treadmill on upper limb vascular mechanics in healthy young men. Issue 13 (12th July 2016) - Olver, T. Dylan; Reid, Steph M.; Smith, Alan R.; Zamir, Mair; Lemon, Peter W. R.; Laughlin, M. Harold; Shoemaker, J. Kevin
Abstract: Interval sprint exercise performed on a manually propelled treadmill, where the hands grip the handle bars, engages lower and upper limb skeletal muscle, but little is known regarding the effects of this exercise modality on the upper limb vasculature. We tested the hypotheses that an acute bout of sprint exercise and 6 weeks of training induces brachial artery (BA) and forearm vascular remodeling, favoring a more compliant system. Before and following a single bout of exercise as well as 6 weeks of training three types of vascular properties/methodologies were examined in healthy men: (1) stiffness of the entire upper limb vascular system (pulse wave velocity (PWV); (2) local stiffness of the BA; and (3) properties of the entire forearm vascular bed (determined by a modified lumped parameter Windkessel model). Following sprint exercise, PWV declined ( P  < 0.01), indices of BA stiffness did not change ( P  ≥ 0.10), and forearm vascular bed compliance increased and inertance and viscoelasticity decreased ( P  ≤ 0.03). Following manually propelled treadmill training, PWV remained unchanged ( P  = 0.31), indices of BA stiffness increased ( P  ≤ 0.05) and forearm vascular bed viscoelasticity declined ( P  = 0.02), but resistance, compliance, and inertance remained unchanged ( P  ≥ 0.10) compared with pretraining values. Sprint exercise induced a more compliant forearm vascular bed, without altering indices of BA stiffness. These effects were transient, as following training the forearm vascular bed was not more compliant and indices of BA stiffness increased. On the basis of these data, we conclude that adaptations to acute and chronic sprint exercise on a manually propelled treadmill are not uniform along the arterial tree in upper limb. Abstract : Interval sprint exercise performed on a manually driven treadmill causes an acute shift in forearm vascular mechanical function toward a more compliant vascular bed without concurrent changes in brachial artery compliance. However, following 6 weeks of training forearm vascular bed compliance remained unchanged and brachial artery compliance decreased. Therefore, acute and chronic vascular adaptations were not directionally consistent with one another and vascular adaptations induced by interval sprint exercise training on a manually propelled treadmill were not uniform along the arterial tree of the upper limb.